Splenogonadal fusion in a 9-year-old patient: a case report - Axelle Boudon; Olivier Hild; Yann Chaussy (Journal of Pediatric Surgery Case Reports, 2025)
Introduction: Splenogonadal fusion is a rare, benign congenital anomaly characterized by an abnormal connection between the spleen and a gonad. Its occurrence is rarely reported in pediatric surgical literature. Case presentation: We present a case of splenogonadal fusion in a 9-year-old patient, which was discovered incidentally during surgery for undescended testis. His only prior condition was an anomaly of the distal right lower limb characterized by right lateral longitudinal ectromelia. Inguinal exploration revealed the left testicle within the inguinal canal. Dissection of the spermatic vessels and vas deferens exposed an unusual fibrous structure attached to the upper pole of the testis. Applying gentle traction on this fibrous cord revealed a splenic-like structure in the inguinal canal. The left testicle was successfully descended into the scrotum without sectioning the fibrous connection. Postoperative recovery was uneventful. At a three-month follow-up visit, the left testicle was palpable in the upper part of the scrotum. To further investigate the congenital anomaly, a contrast-enhanced abdominopelvic computed tomography scan was performed postoperatively. This scan revealed a typical main spleen structure in its usual position in the left hypochondrium, extending into a cord of splenic tissue arising from its lower pole, coursing along the left paracolic gutter and entering the deep inguinal ring. The vascularization of the splenic tissue showed no abnormalities. Conclusion: Splenogonadal fusion is often asymptomatic and is usually discovered incidentally during inguinal exploration for an inguinal hernia or undescended testis. Some anatomical forms are associated with congenital defects of the lower extremities.